Visual Blood Loss Estimation Accuracy: Directions for Future Research Based on a Systematic Literature Review. (December 2020) - Phillips, Rachel; Friberg, Marc; Lantz Cronqvist, Mattias; Jonson, Carl-Oscar; Prytz, Erik
Visual blood loss estimation occurs in a variety of medical contexts and may impact everything from interventions by immediate responders to the likelihood of receiving blood transfusions in a hospital setting. However, research suggests that visual blood loss estimation is inaccurate for laypeople and medical professionals. The aim of the current study was to conduct a systematic literature review to determine the current state of knowledge on visual blood loss estimation accuracy and identify directions for future research. A structured search resulted in 1799 titles that were subsequently screened. A total of 72 articles were coded for comparison. Based on the evaluation, several gaps were identified, most notably related to factors of the situation that may influence estimation accuracy such as blood flow and victim/patient gender. Directions for future research are proposed based on identified gaps.